2010
DOI: 10.1590/s0100-84042010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Pollination and fruit set in pumpkin (Cucurbita pepo) by honey bees

Abstract: and 1997 to determine "Howden" pumpkin (Cucurbita pepo L.) pollen removal and deposition by honeybees and factors relating to male flower attractiveness. Several parameters were evaluated in flowers at anthesis: (1) removal of pollen from anthers by honey bees, (2) pollen deposition on the stigma by honey bees, (3) amount of pollen on the body of honey bees, (4) fruit set after bee pollination, and (5) male flower nectary's pores and flower attractiveness. Honey bees carried between 1,050 to 3,990 pollen grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 16 publications
2
36
1
11
Order By: Relevance
“…In an assessment of the importance of bees for Aodai cucumber production, Nogueira- Couto and Calmona (1993) concluded that honey bees facilitate cucumber fruit set due to their visits to the flowers, thus promoting pollination. Africanized bees can efficiently pollinate several species of the genus Cucurbita (FREE, 1993;NICODEMO et al, 2009, VIDAL et al, 2010.…”
Section: Resultsmentioning
confidence: 99%
“…In an assessment of the importance of bees for Aodai cucumber production, Nogueira- Couto and Calmona (1993) concluded that honey bees facilitate cucumber fruit set due to their visits to the flowers, thus promoting pollination. Africanized bees can efficiently pollinate several species of the genus Cucurbita (FREE, 1993;NICODEMO et al, 2009, VIDAL et al, 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Baik bunga jantan maupun betina memiliki masa anthesis yang berlangsung selama satu hari (Loy 2004). Jumlah biji yang dihasilkan dari proses penyerbukan pada Cucurbit sangat ditentukan oleh jumlah serbuk sari yang diterima oleh putik (pollen limited) sehingga hubungan antara deposit serbuk sari oleh polinator spesifik dan kesuksesan penyerbukan dapat diukur secara langsung (Walters & Taylor 2006). Baik bunga jantan maupun betina, pada Cucurbit mulai mekar sekitar pukul 05:00-06:00.…”
Section: Pendahuluanunclassified
“…Vidal et al (2010) studying the pollination and set fruit in Cucurbita pepo by honyebees reported that percentage of set fruit was maximum (100%) www.intechopen.com when the flowers received 12 visits of A. mellifera, corresponding to load of 1.253 pollen grains deposited on the stigma. In comparision, with two visits of honeybees, 174 pollen grains were deposited on the stigma, and the set fruit only of 50%.…”
Section: Pollination and Plant Reproductionmentioning
confidence: 99%
“…In comparision, with two visits of honeybees, 174 pollen grains were deposited on the stigma, and the set fruit only of 50%. Other important factor is the attraction by pollen and nectar of male flower was arised by opening grade of nectary pore of flower (Vidal et al, 2010).…”
Section: Pollination and Plant Reproductionmentioning
confidence: 99%